Novel Regulator of Acylated Ghrelin, CF801, Reduces Weight Gain, Rebound Feeding after a Fast, and Adiposity in Mice - Wellman, Martin K.; Patterson, Zachary R.; MacKay, Harry; Darling, Joseph E.; Mani, Bharath K.; Zigman, Jeffrey M.; Hougland, James L.; Abizaid, Alfonso (Frontiers in Endocrinology, 2015)
Ghrelin is a 28 amino-acid hormonal peptide that is intimately related to the regulation of food intake and body weight. Once secreted, ghrelin binds to the growth hormone secretagogue receptor-1a (GHSR-1a), the only known receptor for ghrelin and is capable of activating a number of signaling cascades ultimately resulting in an increase in food intake and adiposity. Because ghrelin has been linked to overeating and the development of obesity, a number of pharmacological interventions have been generated in order to interfere with either the activation of ghrelin or interrupting ghrelin signaling as a means to reducing appetite and decrease weight gain. Here we present a novel peptide, CF801, capable of reducing circulating acylated ghrelin levels and subsequent body weight gain and adiposity. To this end, we show that IP administration of CF801 is sufficient to reduce circulating plasma acylated ghrelin levels. Acutely, intraperitoneal injections of CF801 resulted in decreased rebound feeding after an overnight fast. When delivered chronically decreased weight gain and adiposity without affecting caloric intake. CF801, however, did cause a change in diet preference, decreasing preference for a high fat diet and increasing preference for regular chow diet. Given the complexity of ghrelin receptor function, we propose that CF801 along with other compounds that regulate ghrelin secretion may prove to be a beneficial tool in the study of the ghrelin system, and potential targets for ghrelin based obesity treatments without altering the function of ghrelin receptors.